Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The complex logarithm

  1. Jan 26, 2007 #1
    1. The problem statement, all variables and given/known data
    Show that

    [tex] ln(z^\alpha) = \alpha ln(z) [/tex]

    where 'z' and 'alpha' are complex.

    2. Relevant equations
    [tex]ln \alpha = ln r + i(\theta + 2*n*\pi) [/tex]

    3. The attempt at a solution
    For the left hand side I have [tex] ln (z^\alpha) = ln [(r_{1}e^(i\theta_{1}))^(r_{2}e^(i\theta_{2}))][/tex]

    and for the right [tex] \alpha ln(z) = \alpha [ln r + i(\theta + 2 n \pi)] [/tex]

    I have played with it for a bit but seem to be going in circles...
    Any tips/hints would be greatly appreciated! Thank you!
  2. jcsd
  3. Jan 27, 2007 #2
    We know first of all that in the Complex Field, the exponential and logarithmic function are still natural inverses of one another. We define for the logarithmic function the principle branch to ensure analyticity.

    let modulus(z) = |z| and argument(z) = arg(z)

    We first show that exp is the inverse of log.

    [tex]log z = log |z| + i.arg(z)[/tex], so that

    [tex]e^{log z} = e^{log z}e^{i.arg(z)} = |z|e^{i.arg(z)}=z[/tex] by definition

    Conversely, let z = x + iy

    [tex]=log(e^x e^{iy})[/tex]
    [tex]=log |e^x e^{iy}| + i.arg(e^x e^{iy})[/tex]
    [tex]=log(e^x) + iy[/tex] where log(e^x) is the real logarithm
    [tex]=x+iy = z[/tex]

    We then know that [tex]z^\alpha = e^{\alpha log(z)}[/tex]

    since we can expand
    [tex]e^{\alpha log(z)} = \displaystyle\left( e^{log(z)} \right)^\alpha[/tex]

    Thus since [tex]z^\alpha = e^{\alpha log(z)}[/tex] then
    [tex]log(z^\alpha) = log(e^{\alpha log(z)} ) = \alpha log(z) [/tex]

    as required.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook